The Historical Development and Site Value of the Imperial Porcelain Factory in Jingdezhen, China - Ye, Zhenglong; Ruangchewin, Puvasa; Panthupakorn, Poradee (International Journal of Multidisciplinary in Management and Tourism, 2024)
Located in Jingdezhen, Jiangxi, China, the Imperial Porcelain Factory is the longest-running, largest, and most exquisite official kiln factory in Chinese history. Its ruins are also the official kiln ruins with the largest number of relics discovered in China, the richest variety, and the most complete preservation of ruins. After years of conservation and development, the ruins of the imperial porcelain factory were transformed into a national archaeological site park in 2013, which entered a new stage in the protection and utilization of cultural heritage. In 2019, Jingdezhen City integrated cultural heritage resources with the ruins of the imperial porcelain factory as the core. It began the World Cultural Heritage application process, which is currently under active promotion. Based on documentary research methods, this study collects relevant data, sorts out the historical development of the imperial porcelain factory site, and discusses the value content of the imperial porcelain factory site through qualitative analysis. In terms of the research results, the historical development of the Imperial Porcelain Factory is outlined in various stages, and the value content of the ruins is analyzed and summarized from three aspects of history and culture, scientific research and archaeology, and tourism economy, to provide reliable theoretical support and data assistance for subsequent related research.